Odraščanje v Južni Koreji Feministične etnografije transgresije - Pužar, Aljoša (Prostor, kraj, čas, 2019)
This feminist monograph accommodates a selection of ethnographic voices pertaining to the adolescence and young adulthood of South Korean women. The work encompasses secret dimensions of female lives, carefully studying the realm of unexpected physical and social movements, events, bursts of energy, all entailing, to various degrees, what cultural studies and feminist theory usually think of as agency and resistance. Book tackles a notion of transgression (breaching, infringement), tries to locate and present the perceived specificities of South Korean female transgressions, and, finally, it discusses and re-affirms the position of ethnography in the intellectual projects of cultural studies after the affective turn.